Basal lamina remodeling at the skeletal muscle stem cell niche mediates stem cell self-renewal - Shantisree Sandeepani Rayagiri (Nature Portfolio, 2018)
Extracellular matrix (ECM) remodelling is thought to have effects on muscle stem cells that support muscle homeostasis. Here the authors show ECM remodeling controls satellite cell self-renewal through deposition of laminin-α1 into the satellite cell niche.